UNFOLDING VALUES OF JAVANESE CULTURAL WISDOM IN JIDOR SENTULAN JOMBANG: AN ETHNOLINGUISTIC STUDY - Susi Darihastining; Maryaeni Maryaeni (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2017)
Study on language and culture put language as an act and means to fulfill the act. As an act and the means, language conveys many functions. Ideology functions are one of language function resulted from an assumption that particular language feature conveys ideology dimension of a society, in Santoso (2007). Ideology is a reflection of social values which are a consensus. Jidor Sentulan is a literary performance done through dialogic narrating through which tradition and culture are held firmly. This study aimed at describing ideology function of Jidor Sentulan in Jombang. Ethno linguistic analysis describes some language features to reveal values of Javanese cultural wisdom as the ideology of people in Jombang. Results of the study found several language features that represent the values of Javanese cultural wisdom found in Sentulan Jidor of Jombang, they are: (1) lexical process includes (i) lexicalization, (ii) less lexical, and (iii) more lexical; and (iv) modalities, implicature, and terms of address. (2) Awareness functions include (i) function of friendship and brotherhood, (ii) function of the spirit and hard work, (iii) function of social care for the environment, and (iv) function of ideology and religious. The results of the study might be useful to preserve values of local wisdom.